Students' difficulties: mathematical creative thinking skill questions based on habits of mind. - Fineldi, Rira Jun; Hidayati, Kana (Jurnal Riset Pendidikan Matematika, 2023)
This study aims to describe the types of difficulties experienced by students in solving mathematics problems based on students' mathematical creative thinking ability and habits of mind. This research included survey research with quantitative and qualitative approaches. The subjects of the study were 519 students of State Junior High School and State Madrasah Tsanawiyah who came from ten schools with high, medium, and low accreditation categories in Kampar Regency, Riau, Indonesia. The sample in this study was determined by stratified proportional random sampling technique. The instruments used were a diagnostic test consisting of four mathematical problems based on mathematical creative thinking skills and a habits of mind questionnaire consisting of 40 statements referring to 16 habits of mind indicators. Students who obtained diagnostic test scores less than the KKM set by each school. Interviews were conducted with students who experienced difficulties to clarify the types and locations of difficulties experienced by students. The results of the study showed that; 35.26% have difficulties in understanding the problems, 53.76% in transforming problems, 54.38% in the mathematical process, and 54.82% in determining the final answer, and judging from the habits of mind, the very high category is 38.42%, the high category by 44.91%, the medium category by 50.74%, the low category by 53.06%, and the very low category by 52.45%. Students still have difficulty in solving math problems so making the teacher an active facilitator of students can help students understand and determine what steps to take towards difficulties in solving problems.